Investigation of antibiotic resistance, bacteriocin and enzyme production of haloversatile bacteria in salt used for skin preservation, controlling with an antimicrobial substance - Abdulhusein, Haider Sabah (My University, 2023)
Bu çalışmada 25 adet tuz örneği Tuzla/ İstanbul’da bulunan üç tane deri fabrikasından toplanmıştır. Tuz örneklerinin pH’ı 7.60 ve 8.04 arasında saptanmıştır. Toplam haloversatil bakteri sayısı, toplam proteolitik haloversatil bakteri sayısı ve toplam lipolitik haloversatil bakteri sayısı sırasıyla 6×103-1.3×105 KOB/ g, 1×103-7×103 KOB/ g, 2×103-3.1×104 KOB/ g olarak bulunmuştur. Toplam 35 adet haloversatil bakteri [Staphylococcus epidermidis (6 izolat), Staphylococcus warneri (2 izolat), Corynebacterium aurimucosum (2 izolat), Staphylococcus caprae (2 izolat), ve sadece birer izolat Staphylococcus pasteuri, Peribacillus frigoritolerans, Staphylococcus haemolyticus, Lysinibacillus telephonicus, Kocuria rosea, Paenibacillus illinoisensis, Kocuria Polaris, Bhargavaea ginsengi, Bacillus haynesii, Bacillus sonorensis, Bacillus licheniformis, Pseudomonas oryzihabitans, Bacillus subtilis, Bacillus piscis, Staphylococcus hominis, Micrococcus yunnanensis, Staphylococcus saccharolyticus, Pseudomonas iranica, Micrococcus luteus, Staphylococcus capitis subsp. urealyticus, Corynebacterium minutissimum, Bacillus paralicheniformis, Staphylococcus taiwanensis türleri] tuz örneklerinden izole edilmiştir ve 16S rRNA gen dizilemesi ile moleküler olarak tanımlanmıştır. Tüm izolatlar Bacteria Domainine ait olarak bulunmuştur. Sadece iki tane tür [Pseudomonas oryzihabitans (PSS14a) ve Pseudomonas iranica (PSS21a)] Gram-negatif iken, kalan diğer 33 izolat Gram-pozitiftir. Haloversatil türler üç şubede sınıflandırılmıştır: Firmicutes, Actinomycetota ve Proteobacteria. Staphylococcus sp. (16 izolat), Bacillus sp. (6 izolat), Peribacillus sp. (1 izolat), Lysinibacillus sp. (1 izolat), Paenibacillus sp. (1 izolat), ve Bhargavaea sp. (1 izolat) cinslerine ait izolatlar Firmicutes şubesinin üyeleridir. Pseudomonas cinsine ait iki izolat Proteobacteria şubesine ait olarak saptanmıştır. Actinomycetota şubesinde Corynebacterium sp. (3 izolat), Kocuria sp. (2 izolat), and Micrococcus sp. (2 izolat) cinslerine ait toplam yedi adet izolat bulunmuştur. Tüm izolatlara yeni erişim numaraları alınarak NCBI ve GenBank Nükleotid Veritabanlarına kaydedilmiştir. Haloversatil izolatların hidrolitik enzim üretme yetenekleri araştırılmıştır. Enzimatik sonuçlar esteraz, üreaz, proteaz, kazeinaz, lipaz, ksilanaz, selülaz, amilaz, DNaz ve oksidaz enzimlerinin sırasıyla izolatların %40, %66, %77, %6, %17, %6, %17, %20, %20 ve %40’ü tarafından üretilmiştir. İzolatların tamamı katalaz üretirken, hiçbir izolatın pullulanaz üretmediği görülmüştür. Ayrıca, lipaz üretimi için optimum koşulların Tween 80 Besiyerinde pH 7-8 değerinde, 1%-3% NaCl konsantrasyonda, 24-96 saatlik inkübasyon süresi boyunca, 37oC-50oC sıcaklıkta 30 dakikalık su banyosunda bekletme olduğu saptanmıştır. Lipaz ve proteaz enzimlerinin miktarları Bradford Metodu ile belirlenmiştir. Staphylococcus warneri (PSS1a), Staphylococcus pasteuri (PSS1b), Staphylococcus warneri (PSS2a), Paenibacillus illinoisensis (PSS7a) ve Bacillus subtilis (PSS16a) tarafından üretilen enzim miktarları sırasıyla 15.5 µg/ ml, 13.25 µg/ ml, 12.75 µg/ ml, 12.5 µg/ ml ve 12 µg/ ml olarak saptanmıştır. Proteaz enzim miktarı Staphylococcus warneri (PSS1a) için 3.25 µg/ ml, Staphylococcus epidermidis (PSS3a) için 2.5 µg/ ml, Staphylococcus epidermidis (PSS3b) için 2.25 µg/ ml, Peribacillus frigoritolerans (PSS4a) için 1.75 µg/ ml, Bacillus haynesii (PSS11b) için 1.75 µg/ ml, Bacillus subtilis (PSS16a) için 1.5 µg/ ml, Micrococcus yunnanensis (PSS18b) için 2 µg/ ml, Staphylococcus saccharolyticus (PSS20a) için 2 µg/ ml, Staphylococcus epidermidis (PSS24a) için 2.5 µg/ ml olarak bulunmuştur. Haloversatil izolatlar farklı şeker ve amino asit kaynaklarını kullanmıştır. Sırasıyla dekstroz, fruktoz, riboz, sellobiyoz ve sukroz izolatların 91%, 94%, 77%, 77% ve 91%’i tarafından kullanılmıştır. İzolatarın tümü L-tirozin, L-prolin ve L-valini kullanmıştır. İzolatların %9 ve %14’ü sırasıyla L-lizin ve L-arjinin kullanılmıştır. Staphylococcus, Corynebacterium, Micrococcus, Kocuria ve Bhargavaea cinslerine ait türler hareketsiz iken diğer türler hareketliydi. Hücre şekilleri basil, çomak veya pleomorfikti. Optimum gelişim tüm izolatlar için pH 7, 1.17% NaCl, ve 35℃ sıcaklıkta tespit edilmiştir. Corynebacterium aurimucosum (PSS2b), Bacillus haynesii (PSS11b), Staphylococcus epidermidis (PSS3a) ve Peribacillus frigoritolerans (PSS4a) türleri yüksek bakteriyosin üretirken, Bacillus subtilis (PSS16a), Microccus luteus (PSS21b) ve Paenibacillus illinoisensis (PSS7a) izolatları bakteriyosin üretemedi. Corynebacterium aurimucosum (PSS2b)’a ait bakteriyosinden etkilenen Bacillus piscis (PSS17a) izolatının etrafında 9 mm’lik inhibisyon zonu oluşmuştur. En düşük inhibisyon zonu (4 mm) sırasıyla Corynebacterium aurimucosum (PSS2b), Bacillus haynesii (PSS11b), Pseudomonas iranica (PSS21a), Pseudomonas iranica (PSS21a) izolatlarının bakteriyosinlerinden etkilenen Pseudomonas iranica (PSS21a), Staphylococcus warneri (PSS1a), Bacillus haynesii (PSS11b) etrafında ölçülmüştür. Koyun ve keçi derileri proteaz-lipaz üreten Staphylococcus warneri (PSS1a), Staphylococcus pasteuri (PSS1b), Staphylococcus warneri (PSS2a), Paenibacillus illinoisensis (PSS7a), Bacillus licheniformis (PSS13a), Bacillus subtilis (PSS16a); proteaz üreten Staphylococcus epidermidis (PSS3b), Bhargavaea ginsengi (PSS11a), Bacillus sonorensis (PSS12a), Bacillus haynesii (PSS11b), Corynebacterium aurimucosum (PSS15a) izolatların karışık kültürleri ile muamele edilerek 40 gün 24oC’de depolanmıştır. Koyun ve keçi derilerindeki zararlı etkiler taramalı elektron mikroskobunda incelenmiştir. Bu zararlı etkiler, kıl dökülmesi, gözenekler, delikler, liflerin kopması, deri yapısındaki morfolojik değişiklikler olarak saptanmıştır. Tüm izolatlar Rifampisin (RD5, 5 µg), Amikasin (AK30, 30 µg) ve Neomisin (N30, 30 µg) antibiyotiklerinden etkilenmiştir. Sodyum dimetilditiyokarbamet içeren antimikrobiyal maddenin 22 farklı konsantrasyonu (0.00175, 0.0035, 0.007, 0.014, 0.028, 0.06, 0.12, 0.24, 0.48, 0.96, 1.96, 3.92, 7.8, 15.6, 31.2, 62.5, 125, 250, 500, 1000, 2000, 4000 µg/ ml) Staphylococcus warneri (PSS1a), Staphylococcus pasteuri (PSS1b), Paenibacillus illinoisensis (PSS7a), Bacillus subtilis (PSS16a), Micrococcus luteus (PSS21b), Staphylococcus epidermidis (PSS15b), Bacillus sonorensis (PSS12a), Corynebacterium aurimucosum (PSS15a), ve Staphylococcus capitis subsp. urealyticus (PSS22a) izolatlarına karşı uygulanmıştır. Tüm test bakterilerinin gelişimleri (Staphylococcus warneri isolate PSS1a dışında) 125 µg/ ml-4000 µg/ ml konsantrasyonlarında inhibe edilmiştir. Staphylococcus warneri (PSS1a), Staphylococcus pasteuri (PSS1b), Paenibacillus illinoisensis (PSS7a), Bacillus subtilis (PSS16a), Micrococcus luteus (PSS21b), Staphylococcus epidermidis (PSS15b), Bacillus sonorensis (PSS12a) izolatlarının MİK değerleri sırasıyla 250 µg/ ml, 62.5 µg/ ml, 15.6 µg/ ml, 7.8 µg/ ml, 125 µg/ ml, 15.6 µg/ ml, 62.5 µg/ ml olarak bulunmuştur. Corynebacterium aurimucosum (PSS15a) ve Staphylococcus capitis subsp. urealyticus (PSS22a) izolatlarının MİK değeri 3.92 µg/ ml olarak bulunmuştur. Test bakterileri arasında bu iki izolat en düşük konsantrasyonda inhibe olduğu halde, Staphylococcus warneri (PSS1a) bu antimikrobiyal maddeye en dirençli tür olarak saptanmıştır.

INVESTIGATION OF ANTIBIOTIC RESISTANCE, BACTERIOCIN AND ENZYME PRODUCTION OF HALOVERSATILE BACTERIA IN SALT USED FOR SKIN PRESERVATION, CONTROLLING WITH AN ANTIMICROBIAL SUBSTANCE In the present study, 25 salt samples were collected from three leather industries in Tuzla/ Istanbul. The salt samples’ pH values were determined as between 7.60 and 8.04. The total numbers of haloversatile bacteria, the total numbers of proteolytic haloversatile bacteria and the total numbers of lipolytic haloversatile bacteria were respectively found as 6×103-1.3×105 CFU/ g, 1×103-7×103 CFU/ g, 2×103-3.1×104 CFU/ g. Totally 35 haloversatile bacterial [Staphylococcus epidermidis (6 isolates), Staphylococcus warneri (2 isolates), Corynebacterium aurimucosum (2 isolates), Staphylococcus caprae (2 isolates), and only one isolate of the species Staphylococcus pasteuri, Peribacillus frigoritolerans, Staphylococcus haemolyticus, Lysinibacillus telephonicus, Kocuria rosea, Paenibacillus illinoisensis, Kocuria polaris, Bhargavaea ginsengi, Bacillus haynesii, Bacillus sonorensis, Bacillus licheniformis, Pseudomonas oryzihabitans, Bacillus subtilis, Bacillus piscis, Staphylococcus hominis, Micrococcus yunnanensis, Staphylococcus saccharolyticus, Pseudomonas iranica, Micrococcus luteus, Staphylococcus capitis subsp. urealyticus, Corynebacterium minutissimum, Bacillus paralicheniformis, Staphylococcus taiwanensis] were isolated from salt samples and molecularly identified by Sanger dideoxy sequence methods and 16S rRNA gene sequencing. All isolates were belonged to the Domain Bacteria. While only two species [Pseudomonas oryzihabitans (PSS14a) and Pseudomonas iranica (PSS21a)] were Gram-negative, the remaining 33 isolates were Gram-positive. The haloversatile species have distibuted in three phyla: Firmicutes, Actinomycetota, and Proteobacteria. Staphylococcus sp. (16 isolates), Bacillus sp. (6 isolates), Peribacillus sp. (1 isolate), Lysinibacillus sp. (1 isolate), Paenibacillus sp. (1 isolate), and Bhargavaea sp. (1 isolate) were determined as the members of the Phylum Firmicutes. Two isolates belonging to the Genus Pseudomonas were found as the members of the Phylum Proteobacteria. The Phylum Actinomycetota contained seven isolates such as Corynebacterium sp. (3 isolates), Kocuria sp. (2 isolates), and Micrococcus sp. (2 isolates). All isolates have been recorded in the NCBI and GenBank Nucleotide Databases with accession numbers. The ability of haloversatile isolates to produce hydrolytic enzymes was evaluated. The enzymatic results showed that esterase, urease, protease, caseinase, lipase, xylanase, cellulase, amylase, DNase, and oxidase were respectively produced by 40%, 66%, 77%, 6%, 17%, 6%, 17%, 20%,20%, and 40% of the isolates. While all isolates produced catalase, none of the isolates produced pullulanase. In addition, the optimal conditions for lipase production were found as pH 7-8, 1%-3% NaCl concentrations, an incubation period at 24 hours to 96 hours on Tween 80 Agar Media, and 30 minutes in a water bath, temperature between 37 oC and 50oC. The amounts of lipase and protease enzymes was determined by Bradford Method. The amounts of lipase enzyme produced by Staphylococcus warneri (PSS1a), Staphylococcus pasteuri (PSS1b), Staphylococcus warneri (PSS2a), Paenibacillus illinoisensis (PSS7a), and Bacillus subtilis (PSS16a) were detected as 15.5 µg/ ml, 13.25 µg/ ml, 12.75 µg/ ml, 12.5 µg/ ml, and 12 µg/ ml. The amounts of protease enzyme were determined for Staphylococcus warneri (PSS1a) as 3.25 µg/ ml, for Staphylococcus epidermidis (PSS3a) as 2.5 µg/ ml, for Staphylococcus epidermidis (PSS3b) as 2.25 µg/ ml, for Peribacillus frigoritolerans (PSS4a) as 1.75 µg/ ml, for Bacillus haynesii (PSS11b) as 1.75 µg/ ml, for Bacillus subtilis (PSS16a) as 1.5 µg/ ml, for Micrococcus yunnanensis (PSS18b) as 2 µg/ ml, for Staphylococcus saccharolyticus (PSS20a) as 2 µg/ ml, and for Staphylococcus epidermidis (PSS24a) as 2.5 µg/ ml. The haloversatile isolates were able to utilize different sugar and amino acid sources. Dextrose, fructose, ribose, cellobiose, and sucrose were respectively used by 91%, 94%, 77%, 77%, and 91% of the isolates. L-tyrosine, L-proline, L-valine were used by all isolates. L-lysine and L-arginine were used by 9% and 14% of the isolates, respectively. Although all species belonging to the Genus Staphylococcus, Corynebacterium, Micrococcus, Kocuria, and Bhargavaea were non-motile, the other isolates were motile. The cell shapes of isolates were bacil, rod, coccus, or pleomorphic. The optimum growth was observed at pH 7, 1.17% NaCl, and 35℃ for all isolates. The results of bacteriocin experiments showed that while Corynebacterium aurimucosum (PSS2b), Bacillus haynesii (PSS11b), Staphylococcus epidermidis (PSS3a) and Peribacillus frigoritolerans (PSS4a) were able to produce high amount of bacteriocin, Bacillus subtilis (PSS16a), Microccus luteus (PSS21b) and Paenibacillus illinoisensis (PSS7a) could not produce bacteriocin. The highest inhibition zone was determined for Bacillus piscis (PSS17a) as 9 mm which was affected by Corynebacterium aurimucosum (PSS2b). The lowest inhibition zone was determined for Pseudomonas iranica (PSS21a), Staphylococcus warneri (PSS1a), Bacillus haynesii (PSS11b) as 4mm which were affected by Corynebacterium aurimucosum (PSS2b), Bacillus haynesii (PSS11b), Pseudomonas iranica (PSS21a), Pseudomonas iranica (PSS21a), respectively. Sheepskin and goatskin samples, treated with the mix culture of enzyme producing haloversatile bacteria [protease and lipase producing Staphylococcus warneri (PSS1a), Staphylococcus pasteuri (PSS1b), Staphylococcus warneri (PSS2a), Paenibacillus illinoisensis (PSS7a), Bacillus licheniformis (PSS13a) and Bacillus subtilis (PSS16a); protease producing Staphylococcus epidermidis (PSS3b), Bhargavaea ginsengi (PSS11a), Bacillus sonorensis (PSS12a), Bacillus haynesii (PSS11b) and Corynebacterium aurimucosum (PSS15a)], were incubated 40 days at 24oC. The deleterious impacts in sheepskin and goatskin were clearly seen under scanning electron microscope. These deleterious effects were hair loose, pores in skin, cutting of skins’ fibers, skin morphological changes. All isolates were affected by Rifampicin (RD5 µg), Amikacin (AK 30µg), and Neomycin (N 30µg). Twenty-two different concentrations of an antimicrobial agent containing sodium dimethyldithiocarbamate (0.00175, 0.0035, 0.007, 0.014, 0.028, 0.06, 0.12, 0.24, 0.48, 0.96, 1.96, 3.92, 7.8, 15.6, 31.2, 62.5, 125, 250, 500, 1000, 2000, 4000 µg/ ml) were applied to Staphylococcus warneri (PSS1a), Staphylococcus pasteuri (PSS1b), Paenibacillus illinoisensis (PSS7a), Bacillus subtilis (PSS16a), Micrococcus luteus (PSS21b), Staphylococcus epidermidis (PSS15b), Bacillus sonorensis (PSS12a), Corynebacterium aurimucosum (PSS15a), and Staphylococcus capitis subsp. urealyticus (PSS22a). The growth of the test isolates were inhibited with the concentrations between 125 µg/ ml and 4000 µg/ ml except Staphylococcus warneri (isolates PSS1a). The MICs of Staphylococcus warneri (PSS1a), Staphylococcus pasteuri (PSS1b), Paenibacillus illinoisensis (PSS7a), Bacillus subtilis (PSS16a), Micrococcus luteus (PSS21b), Staphylococcus epidermidis (PSS15b), Bacillus sonorensis (PSS12a) were found as 250 µg/ ml, 62.5 µg/ ml, 15.6 µg/ ml, 7.8 µg/ ml, 125 µg/ ml, 15.6 µg/ ml, 62.5 µg/ ml. The MICs of Corynebacterium aurimucosum (PSS15a) and Staphylococcus capitis subsp. urealyticus (PSS22a) were determined as 3.92 µg/ ml. While these two species were affected by the lowest concentration of the antimicrobial agent, Staphylococcus warneri (PSS1a) was the most resistant species against this agent.
Derilerin kullanılmasında kullanılantuzda bulunan haloversatil bakterilerin antibiyotik dirençlerinin, bakteriyosin ve enzim üretimlerinin araştırılması, bir antimikrobiyal madde ile kontrolü
Keywords: and Antibiotic; Antimikrobiyal madde; Bacteriocin; Bacteriology; Bakteriyoloji; Bakteryosin; Enzim; Enzyme; Haloversatil Bakteria; Haloversatile bacteria; ve Antibiyotik Anticrobial substance